Solve x2 − 7x + 12 = 0. x = −3, x = −4 x = 3, x = 4 x = 2, x = 6 x = −2, x = −6

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Solve x2 − 7x + 12 = 0. x = −3, x = −4 x = 3, x = 4 x = 2, x = 6 x = −2, x = −6

Linear Algebra
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

factor the left part of the equation
x^2 - 7x + 12 = 0 x^2 -4x - 3x + 12 = 0 now factor the above by grouping
- that means factor x^2 - 4x and - 3x + 12 then simplify

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

I agree
@DarkMoonZ what did you get after following @welshfella directions
Ok wait
x (x - 4) and 3(4-x)
Sorry I had been AFK lol and thanks @welshfella
first one is write notice it -3 x + 12 negative 3
oh ok
so its -3(4-x)
no its -3( x - 4) If you expand that you'll see it comes bakc to -3x + 12 so we got x(x - 4) - 3(x - 4) = 0
Ok
now e can simplify this further because there is (x - 4) in both parts
so take x - 4 out and what have we got left?
-3x=0
or just X = -3
no what i mean by taking x - 4 out is using it as a factor and what left becomes the other factor similar to 3 x + 3y - 3 is common to both 3x and 3y so we take 3 'out' and it becomes a factor 3x + 3y = 3 (x + y) The x+ y becomes the other factor.
oh ok....
x(x - 4) - 3(x - 4) = 0 (x - 4) is common so we take it out and whats left ( the x - 3 0 goes in the other parentheses so we have (x - 4)(x - 3) = 0
now either x - 3 = 0 or x - 4 = 0 making x = 3 , 4
Ok
thanks

Not the answer you are looking for?

Search for more explanations.

Ask your own question